2015
DOI: 10.1530/eje-14-0522
|View full text |Cite
|
Sign up to set email alerts
|

BMI is an important driver of β-cell loss in type 1 diabetes upon diagnosis in 10 to 18-year-old children

Abstract: Objective: Body weight-related insulin resistance probably plays a role in progression to type 1 diabetes, but has an uncertain impact following diagnosis. In this study, we investigated whether BMI measured at diagnosis was an independent predictor of C-peptide decline 1-year post-diagnosis. Design: Multicentre longitudinal study carried out at diagnosis and up to 1-year follow-up. Methods: Data on C-peptide were collected from seven diabetes centres in Europe. Patients were grouped according to age at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 42 publications
2
31
2
Order By: Relevance
“…This is likely because the initial C‐peptide concentration is a reflection of various factors, including age of onset, predisposing genes, β‐cell function deficiency, and insulin resistance. In addition, there are conflicting observations regarding these factors, with some well‐established factors influencing β‐cell function progression, such as age of onset, autoimmune antibody titers, and HLA genotypes, not found to be of prognostic importance in the present study.…”
Section: Discussioncontrasting
confidence: 68%
“…This is likely because the initial C‐peptide concentration is a reflection of various factors, including age of onset, predisposing genes, β‐cell function deficiency, and insulin resistance. In addition, there are conflicting observations regarding these factors, with some well‐established factors influencing β‐cell function progression, such as age of onset, autoimmune antibody titers, and HLA genotypes, not found to be of prognostic importance in the present study.…”
Section: Discussioncontrasting
confidence: 68%
“…In this context, it is interesting to note from the study of Dabelea et al [13] that inverse correlation is seen only in those youth with reduced beta-cell function; however, BMI has been shown as an important driver of beta-cell loss in T1D [41]. …”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51] Fasting blood glucose and glycated haemoglobin (HbA1c) have not increased in children without diabetes during this period because of a marked increase in plasma insulin levels; a persistently increased β-cell workload seems to be required to maintain normoglycaemia in children today because of the increase in their average body weight. 26,52 Even before this period of increased incidence of T1D, it had repeatedly been reported that children affected by T1D were both taller and heavier than corresponding control subjects without diabetes. 53,54 In contrast, therefore, to the prevailing view that T1D develops as a consequence of a severe decline in β-cell mass resulting from T-cell-mediated autoimmunity, an equally likely scenario could be that glucose intolerance develops in a child who is unable to increase the β-cell volume as a means of coping with increasing demands for insulin ( Figure 1B).…”
Section: Insulin Requirements During Childhood and Adolescencementioning
confidence: 99%
“…Alternatively, the precipitating factor could be the observed increase in body weight in children during the same period of time, which has subsequently plateaued in parallel with the changes in the incidence of T1D . Fasting blood glucose and glycated haemoglobin (HbA1c) have not increased in children without diabetes during this period because of a marked increase in plasma insulin levels; a persistently increased β‐cell workload seems to be required to maintain normoglycaemia in children today because of the increase in their average body weight . Even before this period of increased incidence of T1D, it had repeatedly been reported that children affected by T1D were both taller and heavier than corresponding control subjects without diabetes …”
Section: Insulin Requirements During Childhood and Adolescencementioning
confidence: 99%